2020
DOI: 10.1002/cti2.1164
|View full text |Cite
|
Sign up to set email alerts
|

Distinct macrophage phenotypes skewed by local granulocyte macrophage colony‐stimulating factor (GM‐CSF) and macrophage colony‐stimulating factor (M‐CSF) are associated with tissue destruction and intimal hyperplasia in giant cell arteritis

Abstract: Objective To determine the presence and spatial distribution of different macrophage phenotypes, governed by granulocyte macrophage colony‐stimulating factor (GM‐CSF) and macrophage colony‐stimulating factor (M‐CSF) skewing signals, in giant cell arteritis (GCA) lesions. Methods Temporal artery biopsies (TABs, n = 11) from treatment‐naive GCA patients, aorta samples from GCA‐related aneurysms (n = 10) and atherosclerosis (n = 10) were stained by immunohistochemistry targeting selected macrophage phenotypic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 44 publications
(91 reference statements)
2
48
0
Order By: Relevance
“…However, the precise cellular source of the circulating VEGF in GCA patients has not been determined. A close correlation between tissue site and macrophage functional commitment in the vasculitic lesions has recently been confirmed by Jiemy et al, who showed that MMP-9 + macrophages were placed at areas of tissue destruction, while FRβ+ macrophages were positioned in the hyperplastic intima ( 27 ).…”
Section: Innate Immunity In Gcamentioning
confidence: 70%
“…However, the precise cellular source of the circulating VEGF in GCA patients has not been determined. A close correlation between tissue site and macrophage functional commitment in the vasculitic lesions has recently been confirmed by Jiemy et al, who showed that MMP-9 + macrophages were placed at areas of tissue destruction, while FRβ+ macrophages were positioned in the hyperplastic intima ( 27 ).…”
Section: Innate Immunity In Gcamentioning
confidence: 70%
“…Further evidence indicates that the non-classical monocyte subset is the main source of MMP-9 and associated enzymes, in addition to pro-angiogenic factors such as YKL-40 [35,42,43]. Moreover, (classical) monocytes of GCA patients show upregulated CD64 expression but lowered expression of folate receptor β, which is likely a sign of an activated phenotype [41,44].…”
Section: Monocytes In Gcamentioning
confidence: 99%
“…In contrast to CD206+/MMP-9+/YKL-40+ macrophages, FRβ+ macrophages were mainly found in the adventitia and inner-intima, adjacent to CD206+MMP-9+ macrophages [44,61]. FRβ+ macrophages are likely skewed by local M-CSF signals as opposed to GM-CSF signals that have been reported to diminish FRβ expression by macrophages [55,56].…”
Section: Macrophage Heterogeneity and Their Roles In The Vasculopathy Of Gcamentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of new vessels is a complex process involving many types of cells including macrophages. In fact, the overexpression of colony stimulating factor 1 (CSF-1), in a mouse model, resulted in a premature accumulation of macrophages in the hyperplastic lesion, an early angiogenic switch and consequently accelerated the transition to malignancy ( 79 ).…”
Section: The Role Of Angiogenesis In Allmentioning
confidence: 99%